The Use Of Scientific Methods Of Analysis And Synthesis In Teaching Mathematics - Namozovna, Qodirova Mohidil (Literacy: Journal of Education and Social Science, 2024)
This study examines the effectiveness of utilizing scientific methods of analysis and synthesis in teaching mathematics to enhance students’ learning outcomes. The research employs a quantitative approach with a quasi-experimental design, involving two groups of 10th-grade students: an experimental group taught using the analysis and synthesis methods and a control group taught using conventional methods. Data were collected through pretests, posttests, questionnaires, and classroom observations. Statistical analysis, including t-tests, was applied to evaluate the differences in learning outcomes, while descriptive analysis was used to interpret students’ perceptions and engagement. In this study, the implementation of teaching methods in mathematics within our country is critically assessed, alongside reflections on the effectiveness of using scientific methods to present mathematical concepts to students. The findings reveal that the experimental group achieved significantly higher posttest scores compared to the control group. Additionally, students in the experimental group expressed positive perceptions of the teaching approach, and their engagement in classroom activities improved notably. These results highlight the potential of scientific methods, such as analysis and synthesis, to foster deeper understanding and active participation in mathematics education. This research contributes valuable insights for educators aiming to adopt innovative strategies to enhance teaching practices and improve learning outcomes in mathematics.